Bruxism awareness and self-assessment in dental clinical students: a questionnaire-based study - Tuğba Şahin (BMC, 2024)
Abstract Background Bruxism is a recurrent parafunctional habit characterized by clenching or grinding teeth and/or jaw contractions. It is quite common among dental students and is associated with psychosocial factors such as stress and anxiety. This study aimed to compare bruxism awareness and self-assessment among clinical students with and without bruxism. Methods This study included systemically healthy individuals aged 18 to 27 years. Intraoral and extraoral examinations were performed on 128 4th- and 5th-grade dental students with (64) and without bruxism (64), 4th and 5th-grade dental students at Bolu Abant İzzet Baysal University who met the inclusion criteria. The diagnosis of bruxism was based on the 2018 International Consensus and data collected through a validated 33-item questionnaire covering general information and bruxism awareness. The questionnaire included multiple-choice questions on bruxism types, risk factors, symptoms, and impact on periodontal tissues. Statistical analyses were performed via IBM SPSS Statistics, and p < 0.05 was considered statistically significant. Results Clenching and teeth grinding during sleep, tooth wear, muscle fatigue, pain in the temples, jaw pain, joint trismus, neck pain, and jaw joint pain and clenching while awake were significantly different in bruxism patients (p < 0.05). There was no significant difference between the two groups in terms of bruxism type, symptoms, treatment methods, periodontal tissues, occlusal trauma, diagnostic methods, or the relationship between lifestyle and bruxism (p > 0.05). While 71.9% of those diagnosed with bruxism stated that they had bruxism, 68.8% of those who were not diagnosed stated that they did not have bruxism. Conclusion Although dental students are aware of bruxism, their understanding of its multifactorial nature and treatment options needs improvement. Increasing this knowledge could reduce the prevalence of bruxism among dental students and improve patient care. Clinical trial registration The clinical trial was retrospectively registered on ClinicalTrials.gov under the identifier NCT06583044, with a registration date of 03/09/2024. https://register.clinicaltrials.gov/prs/beta/studies/S000EUYA00000023/recordSummary .